2013 Subtalar Arthroereisis Survey: The Current Practice Patterns of Members of the AOFAS. Issue 3 (June 2015) - Shah, Neil S.; Needleman, Richard L.; Bokhari, Omaima; Buzas, David
Background. Subtalar arthroereisis (SA) has been a procedure used for the correction of painful flexible flatfoot deformity in adults and children. Clinical studies of patients who had a SA are sparse and with mixed results and variable indications. The purpose of this study was to determine the current practice among orthopaedic foot and ankle specialists regarding SA.Methods. Web-based questionnaires were e-mailed to members of the American Orthopaedic Foot and Ankle Society (AOFAS). Requested information included demographics and practice patterns in regard to performing SA surgery. A total of 572 respondents completed the survey (32% response rate).Results. A total of 273 respondents (48%) have performed SA. Of this group, 187 respondents (69%) still perform this procedure (33% of total respondents currently perform SA). Of the respondents, 401 (70%) practice in the United States, 40% have performed SA, and 60% of those still perform this procedure. Of non-US respondents, 66% have performed SA, and 80% of those still perform it. The most common US indications are painful congenital flatfoot, posterior tibial tendon dysfunction, and flatfoot associated with accessory navicular.Conclusion. Many doctors have performed SA, and a significant number no longer perform this procedure for various reasons. A greater percentage of non-US practitioners have performed and continue to perform SA than their counterparts in the United States. There is a common list of surgical indications. Most doctors who still perform this procedure have removed the implants, commonly for pain. SA is still being performed in the United States and throughout the world.